BENTUK PEMANFAATAN LAHAN GUA MACAN SUATU KAJIAN PEMUKIMAN SKALA MIKRO - Indah Asikin Nurani (Berkala Arkeologi, 1997)
In this paper, a micro-scale settlement study will be applied to the conditions and problems in the Macan Cave, which is one of the caves in a cave collection in the Jember area. It is hoped that this paper can explain how micro-scale settlements that occur in Macan Cave and the spatial layout applied to the available cave land to support the activities of its inhabitants.